Chemotherapy for the initial treatment of metastatic prostate adenocarcinoma and neuroendocrine carcinoma at diagnosis: real world application and impact in the SEER database (2004 –2018) - Wang, Shihua; Yin, Ming; Wang, Peng; Folefac, Edmund; Monk, J. Paul; Tabung, Fred K.; Clinton, Steven K. (Frontiers in Oncology, 2023)
Background Randomized controlled phase III trials have reported significant improvements in disease response and survival with the addition of chemotherapy to androgen deprivation therapy for men presenting with metastatic prostate cancer. We examined the implementation of such knowledge and its impact within the Surveillance, Epidemiology, and End Results (SEER) database. Method The administration of chemotherapy for men with an initial presentation of metastatic prostate cancer from 2004 to 2018 in the SEER database and its association with survival outcomes was examined. Kaplan–Meier estimates were applied to compare survival curves. Cox proportion hazard survival models were used to analyze the association of chemotherapy and other variables with both cancer- specific and overall survival. Result A total of 727,804 patients were identified with 99.9% presenting with adenocarcinoma and 0.1% with neuroendocrine histopathology. Chemotherapy as initial treatment for men with de novo distant metastatic adenocarcinoma increased from 5.8% during 2004–2013 to 21.4% during 2014–2018. Chemotherapy was associated with a poorer prognosis during 2004–2013 but was associated with improved cancer-specific (hazard ratio (HR) = 0.85, 95% confidence interval (CI): 0.78–0.93, p=0.0004) and overall survival (HR= 0.78, 95% CI: 0.71–0.85, p < 0.0001) during 2014–2018. The improved prognosis during 2014–2018 was observed in patients with visceral or bone metastasis and most impactful for patients aged 71–80 years. These findings were confirmed by subsequent propensity score matching analyses. Furthermore, chemotherapy was consistently provided to 54% of patients with neuroendocrine carcinoma at diagnosis from 2004 to 2018. Treatment was associated with improved cancer-specific survival (HR= 0.62, 95% CI: 0.45–0.87, p=0.0055) and overall survival (HR= 0.69, 95% CI: 0.51–0. 94, p=0.0176) during 2014–2018 but not significant in earlier years. Conclusion Chemotherapy at initial diagnosis was increasingly employed in men with metastatic adenocarcinoma after 2014 and consistent with the evolution of National Comprehensive Cancer Network (NCCN) guidelines. Benefits for chemotherapy are suggested after 2014 in the treatment of men with metastatic adenocarcinoma. The use of chemotherapy for neuroendocrine carcinoma at diagnosis has remained stable, and outcomes have improved in more recent years. Further development and optimization of chemotherapy continues to evolve for men with de novo diagnosis of metastatic prostate cancer.